Peran Orang Tua Dalam Meminimalkan Risiko Bullying Pada Anak-Anak - Putri Adinda Raraswati; Desy Safitri; Sujarwo Sujarwo (Lembaga Pengembangan Kinerja Dosen, 2024)
Adolescence marks a crucial transition from childhood to adulthood, encompassing emotional, social, physical, and psychological growth. However, this period often presents adolescents with psychological hurdles as they navigate self-identity and explore their surroundings. Among these challenges, bullying emerges as a significant concern, globally pervasive, particularly within school environments. Bullying exerts detrimental effects on its victims, precipitating severe psychological disorders such as anxiety, fear, and depression. Thus, the pivotal role of parents in aiding children through this ordeal cannot be overstated. Parents play a crucial role in offering emotional support, recognizing signs of bullying, and fostering effective coping mechanisms. They can cultivate a safe and nurturing atmosphere at home, encouraging engaging activities and participation in supportive communities. Through proper guidance and support, children can bolster their self-assurance and enhance their mental well-being, effectively confronting the adversities of bullying.